Wound healing activity of methanolic extract of the leaves of Crataeva magna and Euphorbia nerifolia in rats - Sovan Pattanaik, Sudam Chandra Si, Abhisek Pal, Jasmin Panda and Siva Shankar Nayak (Journal of Applied Pharmaceutical Science, 2014)
Crataeva magna and Euphorbia nerifolia have been shown to possess hepatoprotective activity and antioxidant property. The present works with these plants were undertaken with the premise that the drug promoting hepatoprotective activity and radical scavenging property could have effect on wound healing also. The wound healing property of the methanolic extract of the leaves of Crataeva magna (CNM) and Euphorbia nerifolia (ENM) were chosen to investigate in excision and incision wound models. The methanolic extracts of the two plants at the dose of 500 mg/kg/day by topically applying method. Healing was assessed by the rate of wound contraction, time until complete epithelialization, incision breaking strength, estimation of hydroxyproline and histopathological parameters. Complete wound contraction was shown by both the plants in the study period. In excision and incision wound models, all the test drugs showed significant (P
Keywords: Crataeva magna, Euphorbia nerifolia, wound healing, Excision and Incision models.